2016
DOI: 10.1016/j.spinee.2016.07.395
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aging on Cervical Parameters in a Normative North American Population

Abstract: Study Design: Retrospective cohort study. Objectives: To investigate age-based changes in cervical alignment parameters in an asymptomatic population. Methods: Retrospective review of a prospective study of 118 asymptomatic subjects who underwent biplanar imaging with 3-dimensional capabilities. Demographic and health-related quality of life data was collected prior to imaging. Patients were stratified into 5 age groups: <35 years, 35-44 years, 45-54 years, 55-64 years, and !65 years. Radiographic measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Iorio et al reported a significant age-related increase in C2–C7 lordosis, C0–C7 lordosis and T1 slope, especially in subjects older than 55 years. [26] Previous research found that the cervical lordosis is related to age. As reported that cervical lordosis becomes most pronounced with the development of the sitting position at age 9 months, [27,28] and that the C3–C7 lordosis angle reach adult like angles at age 14 to 15.…”
Section: Discussionmentioning
confidence: 99%
“…Iorio et al reported a significant age-related increase in C2–C7 lordosis, C0–C7 lordosis and T1 slope, especially in subjects older than 55 years. [26] Previous research found that the cervical lordosis is related to age. As reported that cervical lordosis becomes most pronounced with the development of the sitting position at age 9 months, [27,28] and that the C3–C7 lordosis angle reach adult like angles at age 14 to 15.…”
Section: Discussionmentioning
confidence: 99%
“…This is important, considering the observed change in CL that occurs with longer follow-up times. [20][21][22] In addition, the larger patient sample of our cohort compared with the aforementioned study (308 vs 104) provides superior power for statistical analysis. 19 Our data suggest that correction of cervical sagittal alignment does contribute to improved clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Previous studies have established the relationship between these parameters, with cervical sagittal vertical axis inversely correlated with CL and directly correlated with T1 slope. 21,30…”
Section: Discussionmentioning
confidence: 99%
“…without kyphosis or lordosis). 13 Ames et al proposed that we should keep the T1S-Cl < 15 , C2-7 SVA < 40 mm 1 . Tundo et al suggested that cervical lordosis or neutral alignment should be restored.…”
Section: Introductionmentioning
confidence: 99%